Bio-oil Quality Based on Coconut Carbon Biomass Using Pyrolisis Method - Ratnasari, Rifa; Wardhani, Gladys Ayu Paramita Kusumah; Taufiq, Agus (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
Coconut shells are biomass composed of carbon, hydrogen, oxygen, nitrogen, and other components in small quantities. Biomass can be converted into bio-oil via the pyrolysis method. Bio-oil resulting from pyrolysis has poor quality because it contains oxygen, acid compound, ketone, and ester. To improve the quality of Bio-oil, the pyrolysis process is carried out through a catalytic esterification reaction using a sulfonated H2SO4 coconut shell charcoal catalyst. Bio-oil synthesis is carried out at a temperature of 300–500 ℃. Coconut shell acid catalyst preparation was carried out by activation using HCl and followed by sulfonation of H2SO4 at a temperature of 150℃ for 12 hours. The catalyst was characterized using XRD, FTIR, and SEM. The bio-oil obtained was tested for density, kinematic viscosity, water content, pH, ash content, acid value, Bio-oil composition using GCMS, and metal content using ICP-OES. The results of catalyst characterization show that the formed solid carbon-based catalyst from coconut shells has a graphite crystal structure with a densely porous surface and contains sulfonate functional groups. The yield of bio-oil produced was 6.4%.